Factors affecting immunization coverage in urban slums of Odisha, India: implications on urban health policy - Santosh K. Prusty; Bhuputra Panda; Abhimanyu S. Chauhan; Jayanta K. Das (PAGEPress Publications, 2013)
Infectious diseases are major causes of morbidity and mortality among children. One of the most cost-effective interventions for improved child survival is immunization, which has significant urban-rural divides. Slum dwellers constitute about one-third of Indian population, and most children still remain incompletely immunized. The main purpose of this study was to understand the factors behind partial or non-immunization of children aged 12-23 months in slum areas of Cuttack district, India. Session-based audit and a population-based survey were conducted in the urban slums of Cuttack city, April-June 2012. Total 79 children were assessed and their mothers were interviewed about the nature and quality of immunization services provided. Children fully immunized were 64.6%. Antigen-wise immunization coverage was highest for Bacillus Calmette-Guérin (BCG) (96.2%) and lowest for Measles (65.8%), which indicates high instances of late drop-out. Frequent illnesses of the child, lack of information about the scheduled date of immunization, frequent displacement of the family and lack of knowledge regarding the benefits of immunization were cited as the main factors behind coverage of immunization services. The study showed that there is an urgent need to revise the immunization strategy, especially for urban slums. District and sub-district officials should reduce instances of early and late dropouts and, in turn, improve complete immunization coverage. Community participation, intersectoral co-ordination and local decision making along with supportive supervision could be critical in addressing issues of drop-outs, supply logistics and community mobilization.